Filsafat Ilmu Manajemen dan Implikasi dalam Praktik - Kaukab, Elfan (P4M STIE Putra Bangsa, 2014)
Abstract This paper explains the development of a management practice framework with the philosophy of the social sciences as analysis approach, especially in the field of management as a basic reference. The tendency of epistemological and ontological understanding of managers will give a different perspective to the organization. This framework can be used to construct a taxonomy that is able to identify the philosophical paradigm as the basis in developing good management practices, so that managers can understand the risks that may arise in the organization due to their lack of understanding the fundamentals of philosophy in management science. Four philosophical frameworks that integrate perspectives, research methods, practices, and behaviors in management become new perspective models, i.e. naturalist-agency perspective, naturalist-structuralist perspective, hermeneutic-agency perspective, and hermeneutic-structuralist perspective. Coherent philosophical approach is necessary in the application and development of management practices.